PENGARUH TEORI ORGANISASI NEOKLASIK DALAM PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH SD - Suwanto, Suwanto; Bahri, Syaiful; Syamsuri, Syamsuri; Nasor, M. (Attadib: Journal of Elementary Education, 2024)
Decision making in the context of principals at the elementary school level is a complex process that involves various factors and considerations. Although Neoclassical theory provides a strong view in economic and rationality-based decision making, its application in educational contexts also faces its own challenges. The purpose of this study is to determine the influence of neoclassical theory in the decision making of elementary school principals. This research method uses a descriptive method of Analysis with a type of qualitative research, which is a type of research that describes phenomena or facts on the object under study to take the essence of each phenomenon .The results of  this study show that the application of Neoclassical Theory in the decision-making of elementary school principals can provide a structured and rational approach, providing a rational, efficient, and results-oriented framework. However, it is important to remember that each policy and decision must be tailored to the unique context of the school and the educational values it carries. By combining the principles of Neoclassical Theory with sensitivity to the needs and dynamics of the community, elementary principals can achieve success in creating an optimal educational environment for student development.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//